Peran Pendidikan Islam dalam Membentuk Budaya Tabayyun di Media Sosial Berdasarkan QS. Al-Hujurât Ayat 6 - Femi Dian Pitasari (Journal of Innovative and Creativity, 2026)
This study examines how Islamic Education plays a role in shaping a culture of tabayyun among students in the era of social media, based on Qur’an Surah Al-Hujurat verse 6. The development of digital technology has indeed made access to and distribution of information easier; however, on the other hand, it has also triggered an increase in the spread of hoaxes, slander, and provocation. In this context, the value of tabayyun taught in Islam becomes highly relevant as a guideline for social media users to be more cautious, critical, and responsible. Islamic Education holds a strategic position in instilling these values through moral education, deepening the understanding of the meaning of Qur’an Surah Al-Hujurat verse 6, and cultivating ethical practices in using social media. To minimize the negative impacts caused by the spread of false information (hoaxes), the implementation of several strategic steps is required. These include fostering an attitude of husnudzan (positive thinking), avoiding the habit of instantly accepting and believing information without critical consideration, and applying the principle of tabayyun through processes of clarification and verification to ensure the truth and validity of information before it is disseminated. This process is reinforced through teachers’ exemplary conduct, appropriate learning methods, and the integration of tabayyun values into the curriculum, so that students become accustomed to verifying the accuracy of information before sharing it. The research findings indicate that the implementation of a tabayyun culture in Islamic education not only enhances Islamic digital literacy but also shapes students’ character to be wiser and more ethical in utilizing social media. Thus, Islamic Education plays an important role in building a digital society that is noble in character and responsible in accordance with the guidance of the Qur’an.